Determination of Spatial Zoning of Telecommunication Towers for Control and Supervision in Bogor City - Waryani, Waryani; Mahfudz, Muhamad (Universitas Pakuan, 2024)
The development of information and communication technology has experienced very rapid development, this also affects the services provided by operators in order to support the speed of development of information and communication technology. Information and communication technology cannot be separated from the existence of BTS (base transceiver station) antennas which are a problem, the construction of too many telecommunications tower infrastructure without planning will cause problems that are not good for the spatial planning and beauty of Bogor City. In determining zoning, data is needed from all telecommunications towers standing in Bogor City, then analyzed using the AHP (Analytical Hierarchy Process) method. In order to make it easier to map telecommunications towers, it is combined with GIS (Geographic information system) with the hope that it can be a recommendation for decision making by the Bogor City government. In determining the zoning, namely by taking into account the distance of the tower and data from the coordinate point where the tower stands. Determination of zoning with a range of 5 km each, so that 4 zones are obtained, namely zone-1 at a distance of 5 km for the Central Bogor City sub-district area, zone 2 at a distance of 5.1 km -10 km for the West, East and North Bogor city areas, Zone-3 at a distance of 10.1-15 km for the South Bogor City and Tanah Sareal areas and Zone-4 at a distance above 15.1 km for parts of the South Bogor City and Tanah Sareal areas.